Analysis of Company Financial Performance Perum Jasa Tirta - Yuli Agustina; Wita Ryani Juniar; Heri Pratikto; Ely Siswanto (AIBPM Publisher, 2020)
The purpose of this study is to determine the financial performance of Perum Jasa Tirta I Malang-East Java for the period 2009-2018. This type of research used in this study is a description and the method used to measure financial performance is one of the methods of financial statement analysis. The financial statement analysis method involves several financial ratios namely liquidity ratios, leverage, activity and profitability and is measured based quantitatively data. The results showed that: Information on financial performance is needed in maintaining the company's existence; this is evident from the results Financial performance of Perum Jasa Tirta I, as seen from profitability ratios and leverage ratios, showed excellent performance even though profitability ratios and activity ratios are known to be in poor condition.